Nurse's participation in the care of patients after a blind brainous impact, under long-term care - Zuzanna Tulej; Damian Osiński; Klaudia Jakubowska; Anna Wiśniewska; Bernadeta Jędrzejkiewicz; Paweł Chruściel; Dorota Nalepa; Michał Machul (Kazimierz Wielki University, 2019)
Introduction. The most important principle of long-term care is the complexity of activities performed and supervised by a nurse. Due to the large deficit of nurses on the labor market and the insufficient level of their qualifications, ensuring professional performance of nursing tasks is difficult. Often, such care is required in patients who have had an ischemic stroke. Purpose. The aim of the study was to determine the scope of nursing activities towards a patient after an ischemic stroke in long-term care conditions. Material and methods. In the study conducted on 1.12.2018 and 2.12.2018, the individual case method was used research techniques such as: documentation analysis, interview, measurement, observation were used. The meetings took place in a home environment. The examined patient was a 66-year-old man after an ischemic stroke. The study used research tools such as: Personalized nursing care card developed by employees of the Faculty of Health Sciences of the Medical University of Lublin, Barthel Scale, Glasgow Scale, Norton Scale, BMI Index, Scale of assessment of basic everyday activities ADL, Own test checking the patient's knowledge / guardian, Criteria for care category and VAS Scale. Results. As a result of a thorough analysis of the patient's health situation, three positive and nine negative diagnoses were specified. A nursing care plan has also been developed. Conclusions. A patient after ischemic stroke who is qualified for long-term care requires holistic care and nursing due to a significant deficit of self-care. Keywords: nursing care, patient, stroke, long-term care.